Applying precision feeding to improve the nitrogen efficiency of swine production: a review of possible practices and obstacles - Alessandra Nardina Trícia Rigo Monteiro (Ciência Rural)
ABSTRACT: Optimizing nutrient efficiency is essential in order to increase sustainability of pig production systems, especially where the growing demand for food must be met at an affordable cost, without compromising environmental resources. To make this happen, it is necessary to develop efficient methods to accurately estimate the nutritional requirements of animals, as well as develop equipment and systems that allow for applying such expertise in the production system. Estimating the nutritional requirement of pigs through mathematical models, considering several factors that can impact the requirement, is a key factor to reduce the environmental load from pig production. Likewise, feed formulation and feeding programs, can help to achieve this. In this context, increasing the number of feeding phases in pig production, as well as precision feeding techniques, may be a tool to the esure adequacy of nutritional requirements, since its use can bring economic and environmental benefits.